Improving the Endotracheal Tube Cuff Pressure Control Management Knowledge of Medical and Surgical Intensive Care Nurses - Karaveli Çakir, Selda; Soyer Er, Ozlem; Yilmaz, Elmas (Ovid Technologies (Wolters Kluwer Health), 2025)
The knowledge level of nurses’ endotracheal tube (ETT) cuff pressure control management is important for patient safety. The aim of this study is to assess how the knowledge level of intensive care (ICU) nurses is affected by ETT cuff pressure control training delivered using 2 alternative teaching techniques. The research was conducted with 88 medical and surgical nurses working in ICUs. The nurses in the groups were given education with presentation techniques in line with evidence-based guidelines on ETT cuff pressure control management. In addition to the nurses in the experimental group, 4 one-on-one follow-up visits were made using the demonstration technique. A statistically significant difference was found between the total scores of the knowledge level of ETT cuff pressure control after training in the experimental group and control group (P < .001). It was determined that presentation and demonstration teaching techniques increased the knowledge level of nurses on ETT cuff pressure control management, and the use of demonstration and one-to-one follow-up strategies were most effective.